Prediction of buffalo bull fertility on the basis of sperm motion traits, viability, membrane integrity, heat shock protein (HSP70) expression and fertility associated antigen (FAA) - KUMAR, AJEET; SINGH, JAGIR; KUMAR, G V P P S RAVI; CHEEMA, RANJANA S; PANDEY, A K; SINGH, PAWAN; GHUMAN, S P S; BRAR, P S; GANDOTRA, V K (The Indian Journal of Animal Sciences, 2016)
The present study was conducted on 20 buffalo bulls to predict the fertility on the basis of: (a) Computer assisted semen analysis (CASA) based sperm motion traits, (b) viability, (c) membrane integrity, (d) expression for HSP70, and (e) assessment of fertility associated antigen (FAA). Six frozen semen straws from each buffalo bulls were analyzed for sperm motion traits, viz. individual motility, progressive motility, average path velocity (VAP), straight line velocity (VSL), curvilinear velocity (VCL), amplitude of lateral head deviation (ALH), beat cross frequency (BCF), straightness (STR), linearity (LIN) and sperm size. Viability and hypoosmotic swelling tests (HOST) were also conducted. Heat shock protein 70 (HSP70) expression and quantification was conducted using a real time PCR. Fertility associated antigen (FAA) was assessed in fresh semen from buffalo bulls using test. Fertility trial was conducted on 250 normal cycling buffaloes following estrus synchronization with GnRH-PGF- GnRH protocol. It was concluded that buffalo bull fertility could be best predicted on the basis of sperm motion traits (VCL, VAP, VSL, ALH, LIN), motility, viability, HOST and HSP70 expression. However, FAA assessment in fresh semen did not indicate fertility.